Understanding the development of self-efficacy for physical activity engagement in men after myocardial infarction: a preliminary qualitative study - Abu, Harlinna; Mohamed Ludin, Salizar; Sowtali, Siti Noorkhairina (Pagepress, 2021)
Background: This preliminary finding from a qualitative study examined the process of self-efficacy for the development of physical activity (PA) during myocardial infarction (MI) after recovery. A combination of healthy behaviors, including physical activity is the secondary prevention recommended to reduce the risk of recurrent MI. This study aims to understand how self-efficacy for physical activity is developed in a patient after MI by examining their perceptions and personal adherence to physical activity. Design and Methods: This was a qualitative study and data was collected through semi-structured in-depth recorded phone interviews with eight Malay male participants. They were screened using a questionnaire and participants that met the inclusion criteria were interviewed and were admitted to National Heart Centre, Malaysia between January to June 2019 diagnosed with MI. The data collected were analyzed using NVivo 12 software and thematic analysis was applied. Results: Four preliminary themes emerged from the study: I) beliefs in physical activity; ii) healthy lifestyle: new normal or same old habit; iii) factors determining participation in PA, and iv) physical activity adherence strategies. Conclusions: The results of the studies showed that participants understand the need to maintain physical activity, which helps to maintain a healthy life after MI and prevent recurrent infarction. Strategies for developing self-efficacy for physical activity were also discussed. The need to understand that maintaining physical activity as well as adopting a new normal of healthy habit after MI is crucial in order to maintain the health and prevent recurrence of MI.